Long-term effects of environmental endocrine disruptors on reproductive physiology and behavior - Patisaul, Heather B.; Adewale, Heather B. (Frontiers in Behavioral Neuroscience, 2009)
It is well established that, over the course of development, hormones shape the vertebrate brain such that sex specific physiology and behaviors emerge. Much of this occurs in discrete developmental windows that span gestation through the prenatal period, although it is now becoming clear that at least some of this process continues through puberty. Perturbation of this developmental progression can permanently alter the capacity for reproductive success. Wildlife studies have revealed that exposure to endocrine disrupting compounds (EDCs), either naturally occurring or man made, can profoundly alter reproductive physiology and ultimately impact entire populations. Laboratory studies in rodents and other species have elucidated some of the mechanisms by which this occurs and strongly indicate that humans are also vulnerable to disruption. Use of hormonally active compounds in human medicine has also unfortunately revealed that the developing fetus can be exposed to and affected by endocrine disruptors, and that it might take decades for adverse effects to manifest. Research within the field of environmental endocrine disruption has also contributed to the general understanding of how early life experiences can alter reproductive physiology and behavior through non-genomic, epigenetic mechanisms such as DNA methylation and histone acetylation. These types of effects have the potential to impact future generations if the germ line is affected. This review provides an overview of how exposure to EDCs, particularly those that interfere with estrogen action, impacts reproductive physiology and behaviors in vertebrates.